Tinjauan Kelengkapan Pengisisan Formulir Informed Consent Pada Pasien Bedah Rawat Inap Di Rumah Sakit Sari Mulia Banjarmasin Triwulan Ke-Iv Pada Tahun 2020 - Muhammad Rashif Anshari; Putri Maisyarah; Risnawati Risnawati (Jurnal Kajian Ilmiah Kesehatan dan Teknologi, 2021)
The completeness of filling in informed consent is very important because it will affect the legal aspects of medical records and the quality of medical records so that in its implementation it must be carried out optimally. This study aims to determine the completeness of filling in informed consent for inpatient surgery patients in the fourth quarter of 2020 at Sari Mulia Hospital, Banjarmasin. This study uses descriptive quantitative research with a cross sectional research design, the method used is the observation method using a check list tool. In this study, the sampling technique was random sampling, the number of samples was 141 medical records of inpatient surgical patients analyzed, and all of them were still incomplete. The results obtained that the average number of completeness of filling based on identity review is 100%, important note review is 46.8%, authentication review is 90.7%, good record review is 68%. Where the highest completeness in the identity review is 100% and the lowest completeness is in the important note review, which is 46.8%. Based on the results of the study, it can be concluded that the number of completeness of filling out informed consent forms for inpatient surgical patients at Sari Mulia Hospital Banjarmasin 4th Quarter of 2020 has not reached the SPM for medical records at hospital is 100%.